Shear bond strength between light polymerized hard reline resin and denture base resin subjected to long term water immersion - Mohammad Q. Al Rifaiy (Elsevier, 2012)
Statement of the problem: The effect of long-term water immersion on the shear bond strength between denture base resin and Triad visible-light-polymerized (VLP) direct hard reline resin is not known. Purpose: The aim of this study was to investigate the bonding characteristics of Triad VLP direct hard reline resin to heat-polymerized denture base resin subjected to long-term water immersion. Material and methods: Ninety circular disks, 15 mm in diameter and 3 mm thick, of denture base resin were polymerized from a gypsum mold. Sixty specimens were subjected to water immersion and 30 were stored at ambient room temperature for 4 months. Thirty water-immersed specimens were dried with gauze (group 1), while the other 30 water-immersed specimens were dried with a hair dryer (group 2). The dry specimens (n = 30) represented the control group (group 3). All specimens were air abraded and painted with bonding agent before packing Triad VLP direct hard-reline resin. Specimens in each group were subjected to thermal cycling for 50,000 cycles between 4 °C and 60 °C water baths with 1-min dwell time at each temperature. The bond strength at which the bond failed under stress was recorded using a universal testing machine. One-way ANOVA and Tukey post hoc comparison were applied to find significant differences between groups (α = 0.05). Results: Significant differences in mean shear bond strength among the specimens existed because of variable water content in the denture base resin (P < 0.05). Group 3 (dry) was higher than group 2 (desiccated), and the lowest was group 1 (saturated). Conclusion: The shear bond strength of Triad VLP direct hard reline resin to denture base resin depended on the water content in the denture base resin. The dry denture base resin demonstrated superior bond strength compared with the desiccated and water-saturated denture base resins. Keywords: Shear bond strength, Light polymerized, Hard reline resin, Denture base resin